Supersolidus Sintering And Mechanical Properties Of Water-Atomised M3/2 High-Speed Steel Powder Sintered Under Nitrogen-Based Atmosphere - Selamat, Mohd Asri; Mohamad, Mazlan (Penerbit UTM Press, 2004)

(untitled)
The Ability To Produce Near Net Shape High-Speed Steels Using A Continuous Belt Furnace Offers The Opportunity To Improve The Properties And Reduce The Processing Cost Of These Materials. So Far, The Difficulty In Making This Advancement Has Been The Requirement Of High Sintering Temperatures (1250–1350°C) In Vacuum Atmosphere. A Low Cost-Sintering Route Of Wateratomised High-Speed Steel Powder Has Been Developed During This Project Using Supersolidus Liquid Phase Sintering (SLPS) Mechanism. This Water-Atomised M3/2 High-Speed Steel Powder Can Be Sintered To Full Density (>95% Of Theoretical Density) Under Nitrogen-Based Atmosphere At Sintering Temperature Of 1150°C. Acceptable Microstructures And Mechanical Properties Have Been Obtained After Appropriate Heat Treatment.